موقف شيخ الإسلام ابن تيمية من العصمة النبوية: (The Position of Shaikh al-Islām Ibn Taimiyyah on the al-‘Iṣmah (Sinlessness) of the Prophet) - أسماء محمد توفيق بركات (At-Tajdid - Intellectual Refereed Journal, 2022)
This research aims to analyze the position of Shaikh al-Islām Ibn Taimiyyah on the ‘iṣmah (sinlessness) of the Prophet; through the realization of the concept of infallibility in the law; In order to clarify the approval of the Shaikh al-Islām the sayings of the predecessors, and the research deals with its content, the definition of al-‘Iṣmah linguistically and terminologically, its importance, types, evidence, the position of its opponents, and the response to them. In the meantime, the research uses the descriptive analytical approach, and one of the most important results is to achieve the concept of infallibility in accordance with the evidence from the Qur’an and the Sunnah according to Ibn Taimiyyah’s views, and to highlight everything that has an impact on the statement of the importance and status of al-‘iṣmah, and that it is fixed, and that it is one of the fundamentalist religious facts that entail the eligibility of legislation. The integrity of the followers, the detection of deviation sources in the concept of infallibility, and the extent to which these deviations are related to the approaches of its owners and their doctrinal attitudes in all their diversity. Keywords: Al-‘Iṣmah, prophecy, revelation, Ibn Taimiyyah, belief.